2015
DOI: 10.1002/lt.24062
|View full text |Cite
|
Sign up to set email alerts
|

Changes in liver and spleen volumes after living liver donation: A report from the adult‐to‐adult living donor liver transplantation cohort study (A2ALL)

Abstract: Previous reports have drawn attention to persistently decreased platelet counts among liver donors. We hypothesized an etiologic association between altered platelet counts and post-donation splenomegaly and sought to explore this relationship. This study analyzed de-identified CT/MR scans of 388 donors from 9 A2ALL centers read at a central computational image analysis lab. Resulting liver and spleen volumes were correlated with time-matched clinical lab values. Pre-donation liver volumes varied twofold in he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 26 publications
2
15
0
Order By: Relevance
“…Although many studies have investigated short‐term outcomes following donor hepatectomy, less is known about the longterm outcomes, and to our knowledge, no other study has reported on active screening for late anatomic changes such as occult biliary strictures, splenomegaly, failure to regenerate the native liver, or vascular stenosis. A recently published article from the A2ALL group reported on short‐term changes by comparing CT volumetric data from prior to donation, versus 3 months and 1 year from donation, and found, similar to our study, an increase in spleen size, which was most pronounced at 3 months . Two other recently published studies report satisfactory longterm health outcomes for living donors though they did not include routine use of cross‐sectional imaging .…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Although many studies have investigated short‐term outcomes following donor hepatectomy, less is known about the longterm outcomes, and to our knowledge, no other study has reported on active screening for late anatomic changes such as occult biliary strictures, splenomegaly, failure to regenerate the native liver, or vascular stenosis. A recently published article from the A2ALL group reported on short‐term changes by comparing CT volumetric data from prior to donation, versus 3 months and 1 year from donation, and found, similar to our study, an increase in spleen size, which was most pronounced at 3 months . Two other recently published studies report satisfactory longterm health outcomes for living donors though they did not include routine use of cross‐sectional imaging .…”
Section: Discussionsupporting
confidence: 85%
“…It may be that spleen size increases immediately after donation, due to relative portal hypertension induced by resection, and although the latter improves with time as liver regeneration occurs, the spleen may never return to normal size. This is suggested by the aforementioned report that spleen size increased mostly at 3 months after donation and decreased somewhat at 1 year …”
Section: Discussionmentioning
confidence: 55%
“…Table 4 summarizes the results of important published studies on liver functional and volumetric recovery in right lobe living donors. Regarding the rate of liver function recovery in donors, while some studies show that complete normalization of liver function tests occurs within the first postoperative week (nine studies) (12)(13)(14)(15)(16)(17)(18) or within the first month (13 studies) (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), others show that this takes anywhere between 3 months and 1 year after donor hepatectomy (31)(32)(33)(34)(35)(51)(52)(53)(54). This variance can be attributed in part to the absence of a universal definition for ''liver functional recovery.''…”
Section: Discussionmentioning
confidence: 99%
“…It is critical that we strive to decrease these risks if we are to increase the number of LDLT performed in North America. The A2ALL consortium has detailed data on liver regeneration and recovery in the donor, and found variables associated with better outcomes, and identified issues in the donor including liver function, laboratory tests, psychosocial concerns and quality of life that will require long-term follow-up and merit further study (4549). We should continue to be aware of potential long-term effects of donation, both physical and psychosocial.…”
Section: Discussionmentioning
confidence: 99%